2014
DOI: 10.4103/0331-3131.141026
|View full text |Cite
|
Sign up to set email alerts
|

Benign breast diseases in Warri Southern Nigeria: A spectrum of histopathological analysis

Abstract: A B S T R A C TBackground: Benign breast diseases (BBDs) constitute a source of morbidity and mortality among women globally. Most of these lesions are common in women of reproductive age and are associated with hormonal infl uences. However, studies have reported an increasing incidence of these lesions in children and adolescents. Aims: The aim was to highlight the spectrum and histological patterns of BBDs among women in Delta State and other Southern states of Nigeria as seen at central hospital, Warri. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 6 publications
4
11
3
Order By: Relevance
“…The results of the index study showed that benign breast lesions constituted 68.3% (228) of the total breast lesions (334) studied. This is similar to the findings in other series in Nigeria: in which 67% [ 15 ], 68.8% [ 2 ], 71.2% [ 16 ], 72.5% [ 1 ], 73% [ 17 ] and 73.4% 18 were seen in Markudi, Enugu, Warri, Benin, Kano and Calabar respectively. On the other hand, lower figure of 59.5% [ 19 ] BBD was seen in Gombe while much higher figures of 87% [ 20 ] and 89% [ 1 ] were recorded in Ilesha and Ibadan respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the index study showed that benign breast lesions constituted 68.3% (228) of the total breast lesions (334) studied. This is similar to the findings in other series in Nigeria: in which 67% [ 15 ], 68.8% [ 2 ], 71.2% [ 16 ], 72.5% [ 1 ], 73% [ 17 ] and 73.4% 18 were seen in Markudi, Enugu, Warri, Benin, Kano and Calabar respectively. On the other hand, lower figure of 59.5% [ 19 ] BBD was seen in Gombe while much higher figures of 87% [ 20 ] and 89% [ 1 ] were recorded in Ilesha and Ibadan respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Abhijit et al also reported fibroadenoma as the most common breast disease forming 56.4% of the total benign breast lesions in rural India [ 25 ]. A study in Kano, Northern Nigeria however reported fibrocystic change as the most common BBD with fibroadenoma as the second [ 8 , 16 ]. Also Memon et al [ 26 ] in Pakistan and Shirley et al [ 27 ] in Jamaica both reported fibrocystic change as the most common BBD in their series while another study in Karachi, Pakistan reported fibroadenoma as the most common BBD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study BBDs comprised 54% of all breast lumps. This is lower than 72.4% of 2011 Benin Study [7], 71.2% of 2014 Warri Study [8], and 68.3% of 2014 Bayelsa study [9]. Our figure compared favorably with findings from Gombe, Nigeria with 59.5% [10].…”
Section: Discussioncontrasting
confidence: 65%
“…Two cases of hamartoma (0.31%) were reported by Forae et al, 7 while Pudale S et al 5 reported a single case (0.18%) in their study.…”
Section: Discussionmentioning
confidence: 74%